Analysis of Accountants' Perceptions of the Use of Cloud Accounting in Improving the Accuracy and Efficiency of Financial Statements - Arum, Mega; Kardi, Kardi; Triatmaja, Muhammad Fithrayudi; Hapsari, Nesti; Sudarmanto, Eko (Westscience Press, 2025)
This study investigates accountants’ perceptions of the use of cloud accounting in enhancing the accuracy and efficiency of financial statements. Utilizing a quantitative research design, data were collected from 120 accountants through a structured questionnaire using a 5-point Likert scale. The data were analyzed using SPSS version 25, employing descriptive statistics, validity and reliability tests, correlation analysis, and linear regression. The results indicate that cloud accounting is perceived to significantly improve both the accuracy and efficiency of financial reporting. High correlation values and strong regression results support the positive relationship between cloud accounting usage and financial reporting quality. These findings highlight the strategic importance of cloud-based systems in modern accounting practices and support the adoption of cloud technology to improve organizational performance and transparency.